AB0946 Absence of Infections in Outpatient Ultrasound Guided Musculoskeletal Procedures Performed at A Rheumatology Clinic Using Either Sterile Gel or Iodine Cleaning Solution: Are Sterile Ultrasound Probe Covers Needed?. (10th June 2014) - Abril, A.; Berianu, F.
Abstract : Background: Aspiration and injection of joints has been an integral part of rheumatology practice. Procedures were done blindly using anatomical landmarks and clean techniques. For the last few years, musculoskeletal ultrasonography has been available to guide musculoskeletal injections, providing more accuracy and better outcomes. Efforts have taken place to keep the ultrasound probe as sterile as possible, including using sterile ultrasound probe covers, which are somewhat cumbersome, since gel has to be applied inside cover to provide an interface for the ultrasound waves, and on top of the skin of the target area, creating additional costs and procedure time. Other practitioners sterilize the probe with solutions to minimize the risk of infections, iodine solutions have been also found to provide a good sound wave interface for diagnostic ultrasonography. We have done ultrasound guided procedures at the division of rheumatology of the Mayo Clinic Florida using a thoroughly cleaned and disinfected ultrasound probe, using either a sterile surgical gel or an iodine solution as interface for the ultrasound waves, but we have not used a sterile ultrasound cover. The use of iodine solutions have been determined by manufacturers of ultrasound machines to be safe for the probe. Objectives: The objective of this study, is to assess whether there have been any reported infectious complications related to the use of thoroughly clean ultrasound probes using iodine solutions or sterile gel as interface. Methods: We looked retrospectively at US guided skeletal procedures done at the division of rheumatology, between August 2007 and August 2013, and looked at subsequent visits with any Mayo medical provider, and telephone messages documented in the chart after the procedure, to document any reported infections. Variables included: age of the patient, joint injected, whether an iodine solution (Providone-iodine) or surgical sterile gel was used as ultrasound interface, whether any infections were reported after a subsequent medical visit, and the time elapsed between the procedure and the next visit with a Mayo Clinic provider. Results: 279 procedures were performed under ultrasound guidance, 106 procedures using sterile gel as US interface and 173 procedures used iodine solution as interface. There was follow up done by a Mayo Clinic provider in 254 cases, no infections were reported or identified. The follow up average time after procedure was 24 weeks, (2 days to 3 years). There were 25 cases in which there were no follow-up visits, but it is very likely that there were no infections, since there were no documented patient calls complaining of worsening symptoms the following days or weeks after the procedure. Conclusions: This study suggests that sterilizing the probe thoroughly, keeping a sterile field, a sterile ultrasound probe and using either sterile gel an iodine cleaning solution as interface for the procedure, is a safe, time saving and cost effective way to perform ultrasound-guided procedures a rheumatology. Due to institutional practices, we did not perform hip joint injections. We have not seen damage or decay of the ultrasound probe after 7 years of using these techniques; we immediately cleaned the iodine solution after the procedure with probe-safe disinfecting wipes to avoid staining. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2388